Гіпохолестеролемія при гострому коронарному синдромі: прогностичне значення, особливості перебігу, супутні несприятливі фактори (огляд літератури та власні спостереження) - Королюк, О.; Радченко, О. (Медична гідрологія та реабілітація, 2009)
С целью изучения частоты гипохолестеролемии (гипоХС) у пациентов с острым коронарным синдромом (ОКС) и изучения особенностей течения ОКС у пациентов с низким уровнем ХС проведен обзор литературы и ретроспективный анализ историй болезни 130 пациентов. Выявлено, что гипоХС чаще выявляется у пациентов с острым инфарктом миокарда, особенно в фатальных случаях, и ассоциируется с гипотонией, кардиогенным или аритмичным шоком, острой АВ-блокадой высокой степени, разрывом миокарда, высокими уровнями креатинина и протеинурии, низкими уровнями общего белка и анемией. Особенно опасным является комбинация гипоХС и гипергликемии, в связи с высокой ранней и отдаленной смертностью, большими размерами некроза, высшей частотой осложнений и склонностью к разрывам миокарда. Дискутируется необходимость специальных терапевтических мероприятий коррекции острой гипергликемии при ОКС. Необходимо изучить безопасность проведения тромболизиса у таких пациентов. Acute coronary syndrome (ACS) remains the most frequent cause of morbidity and mortality worldwide. It is known that low serum cholesterol levels are associated with poor prognosis in patients with ischemic heart disease. Literature review, along with retrospective study of 130 patients' medical records, hospitalized due to ACS (49 females and 81 males, aged 41 to 86 years), has been performed in order to elucidate the incidence of hypocholesterolemia and peculiarities of the course of ACS. Patients with unstable angina (n=80) were included into group A, patients with acute myocardial infarction (n=23) entered group B, and 27 patients with fatal complications of ACS composed group . Total serum cholesterol levels lower than <4,1 mmol/l and exceeding >6,2 mmol/l were considered to be hypo- and hypercholesterolemia, respectively. Hypocholesterolemia was found to be significantly more frequent among patients with acute myocardial infarction, especially in fatal cases, and was associated with arterial hypotension, cardiogenic and arrhythmic shock, acute high degree AV block, myocardial rupture, high serum creatinine levels and significant proteinuria, low serum protein levels and anemia. Combination of hypocholesterolemia with acute hyperglycemia in patients with or without prior diabetes were found to be the most dangerous, because of higher early and late mortality rates after acute myocardial infarction, stroke, larger sizes of necrosis, more frequent complications and predisposition to myocardial rupture. Practically, a need of specific therapeutic strategy for correction of acute hyperglycemia in patients with ACS is debated nowadays. Safety of thrombolytic drug therapy in such patients requires further investigations.